IBM Tivoli Monitoring for Network Performance V2.1: The Mainframe Network Management Solution - Redbooks, IBM (I B M, 2004)
This IBM Redbooks publication explains the new IBM Tivoli Monitoring for Network Performance Version 2.1. This version of IBM Tivoli Monitoring for Network Performance provides a complete redesign of the z/OS TCP/IP management tools that is started by the NetView Performance Monitor for TCP/IP.IBM Tivoli Monitoring for Network Performance provides a comprehensive TCP/IP stack monitoring for z/OS. It collects performance metrics from the z/OS Communication Servers system management interface, measuring response time and Simple Network Management Protocol (SNMP) Management Information Base (MIB) variable collection.IBM Tivoli Monitoring for Network Performance uses strategic IBM software platforms such as WebSphere Application Server as the Web application platform and DB2 Universal Database as the central repository.This book starts with exploring on the architecture of IBM Tivoli Monitoring for Network Performance and its components. We also discuss various implementation scenario and evaluate the benefits and drawbacks of each scenario. Implementation planning and consideration is presented and lastly operational consideration is explained.